Parametric analysis of the mechanism of creating indoor thermal environment in traditional houses in Lhasa. (January 2022) - Li, En; Zhu, Jiangkun
Abstract: Traditional Tibetan houses exhibit a response to the unique local climate, reflecting a green wisdom in terms of architectural design. This paper therefore aims to investigate the mechanism of creating indoor thermal environment of traditional houses in Lhasa. Field measurements indicate passive design methods can improve the thermal environment in winter. Simulation was used to analyze the winter comfort time ratio (WCTR) and indoor average temperature on the coldest days of two typical traditional houses. Then parametric analyses were deployed to clarify and rank the effects of individual passive design methods related to architectural form design and thermal design of envelope. Based on the criteria from current regional standard, the WCTR of was 32.1% and 10.7% for the L-shaped house and the oblong-shaped respectively. For the two houses studied, the importance of individual passive design method is different. Specifically, as to the four architectural form design methods, orientation and depth-width ratio (DWR) are two most important methods for the two house types. Additionally, the semi-open space is also considered as a significant method. Regarding the five thermal design methods, the window-wall ratio (WWR) and the external wall thermal resistance are the two most important methods in the two houses. These results contribute to a deepened understanding of the thermal mechanism in traditional houses and of select passive design methods and offer implications for architecture design practice. Graphical abstract: Image 1 Highlights: Passive design methods of traditional Tibetan houses were summarized qualitative by field survey. The influence of all the passive design methods was ranked. Orientation and DWR are the most significant architecture form design methods for Lhasa's traditional houses. WWR and the external wall thermal resistance are the most significant thermal design methods for Lhasa's traditional houses.